Bacteriophage Infection: Which End of the SP82G Genome Goes in First? - McAllister, William T. (1970)
The transfer of deoxyribonucleic acid (DNA) from bacteriophage SP82G to its host may be halted by chilling but is affected little by chloramphenicol, actinomycin D, or cyanide. The order of entry of markers on the phage genome was determined by halting the transfer of DNA at intervals, removing the untransferred DNA by blending, and assaying for the presence of markers in the blended complexes. Markers on the phage genome are transferred in a linear, polar fashion consistent with the previously determined genetic and physical maps. Those markers concerned with early functions enter first, and the rate of transfer is temperature dependent.